Peran Asisten Imam dalam Pendampingan Iman Orang Sakit di Paroki Santa Maria dengan Tidak Bernoda Asal Tulungagung - Marsel Awan; Agustinus Rudi Winarto (Fakultas Teologi, Universitas Sanata Dharma, 2025)
This title was chosen because it sees the role of the assistant priest which is so important in assisting the faith of the sick and seeing the picture of the faith assistance of the sick that has been going on so far. The assistant priest is the spearhead of the church's pastoral ministry work. Assistant priests have many roles in the church. One of them is to provide faith assistance as well as send communion for the sick. The problem that arises is that there are many assistant priests, but there are few who serve the faith assistance of the sick. In response to this problem, the author conducted a research on the role of assistant priests and faith assistance for the sick. Observation was made to see firsthand the role of the assistant priest in assisting the faith of the sick. The author uses qualitative research by conducting in-depth interviews with assistant priests by paying attention to their age and tenure. The selection of informants was carried out on the proposal and discussion with the head of the liturgical section and the coordinator of the assistant priest. The results of the study show that the role of assistant priests in assisting the faith of the sick is very important and missed by the people. However, the provisions owned by this assistant priest still need to be increased, developed, and improved, especially the provisions for faith assistance for the sick. The competence of assistant priests needs to be improved in order to serve well. The faith assistance carried out must be able to bring enthusiasm, motivation, joy, and comfort to the sick and their families. Faith assistance, faith confirmation, and gratitude for the assistant priest who serves. Assisting the faith of the sick is not just a task but a call from the heart.AbstrakJudul ini dipilih karena melihat peran asisten imam yang begitu penting dalam pendampingan iman orang sakit sekaligus melihat gambaran pendampingan iman orang sakit yang telah berlangsung selama ini. Asisten imam adalah ujung tombak karya pelayanan pastoral gereja. Asisten imam memiliki peran yang banyak dalam gereja. Salah satunya adalah memberikan pendampingan iman sekaligus mengirimkan komuni bagi orang sakit. Persoalan yang muncul adalah asisten imam itu banyak, namun yang melayani pendampingan iman orang sakit itu sedikit. Menanggapi pokok permasalahan ini, penulis melakukan penelitian mengenai peran asisten imam dan pendampingan iman orang sakit. Observasi dilakukan untuk melihat secara langsung mengenai gambaran peran asisten imam dalam pendampingan iman orang sakit. Penulis memakai penelitian kualitatif dengan melaksanakan wawancara mendalam dengan asisten imam dengan memperhatikan usia dan masa baktinya. Pemilihan informan dilakukan atas usul dan diskusi dengan ketua seksi liturgi dan koordinator asisten imam. Hasil penelitian menunjukkan bahwa peran asisten imam dalam pendampingan iman orang sakit itu sangat penting dan dirindukan oleh umat. Namun, bekal yang dimiliki oleh asisten imam ini masih perlu ditambah, dikembangkan, dan ditingkatkan, khususnya bekal untuk pendampingan iman orang sakit. Kompetensi asisten imam perlu ditingkatkan agar bisa melayani dengan baik. Pendampingan iman yang dilakukan harus bisa membawa semangat, motivasi, sukacita, dan penghiburan bagi yang sakit dan keluarganya. Pendampingan iman peneguhan iman dan rasa syukur bagi asisten imam yang melayani. Pendampingan iman orang sakit bukanlah sekedar tugas melainkan panggilan dari dalam hati.